The Impact of Combination Therapy with Rivaroxaban and Acetylsalicylic Acid in Patients with Coronary Heart Disease on the Achievement of the Target for Reducing Mortality from Cardiovascular Diseases of the Federal Project "Fight against Cardiovascular Diseases" - M. V. Zhuravleva; A. V. Panov; A. R. Kuksenok (Столичная издательская компания, 2022)
Aim. To assess the outcomes of combination therapy with rivaroxaban and acetylsalicylic acid (ASA) in patients with stable coronary artery disease (CAD) and a high risk of thrombotic events on the set targets of Ministry of Health for reduction of cardiovascular mortality in Russia.Material and methods. The development of the model for analysis in MS Excel included the following stages: calculation of the population of patients with stable CAD who can be treated with combination therapy (rivaroxaban and ASA); calculation of the number of deaths due to cardiovascular disease (CVD), number of strokes and myocardial infarction (MI) in the current scenario (patients receive monotherapy with ASA) and simulated scenario (some patients switch from monotherapy to combination therapy); estimation the impact of the number of avoided cases of deaths due to combination therapy on set target for reducing CVD mortality in 2024 year; sensitivity analysis to assess the sustainability of outcomes.Results. Total number of eligible patients for combination therapy was estimated as 1.08 million patients. Based on the simulation results, it was determined that with the reallocation of patients from monotherapy with ASA to combination therapy with rivaroxaban and ASA, the number of avoided deaths in 2022 will be 973 cases, in 2023 - 1,622 cases, in 2024 - 3,245 cases, which will make it possible to reach 6.7%, 7.4% and 11.1% of the set target for reduction of mortality from CVD in the respective years. In addition, the gradual reallocation of patients from monotherapy to combination therapy might decrease the cases of stroke and MI in 973 and 649 cases by 2022, 1,622 and 1,082 cases by 2023, and 3 245 and 2 163 cases by 2024 year, respectively. Sensitivity analysis showed that outcomes are sustainable.Conclusion. The use of combination therapy of rivaroxaban and ASA in patients with stable CAD and high thrombotic risk will allow to achieve up to 11.1% of the set target for reduction of mortality from CVD by 2024 in Russia and can also potentially impact on another set target for reduction mortality from cerebrovascular diseases by reducing the number of strokes. Thereby, this therapy can be considered for drug provision programmes for patients with stable CAD and high thrombotic risk to fulfill the goals to reduce mortality from CVD.